2019
DOI: 10.1139/gen-2018-0184
|View full text |Cite
|
Sign up to set email alerts
|

Allopolyploid origin and genome differentiation of the parasitic speciesCuscuta veatchii(Convolvulaceae) revealed by genomic in situ hybridization

Abstract: Interspecific hybridization and genome duplication to form allopolyploids are major evolutionary events in angiosperms. In the parasitic genus Cuscuta (Convolvulaceae), molecular data suggested the existence of species of hybrid origin. One of them, C. veatchii, has been proposed as a hybrid between C. denticulata and C. nevadensis, both included in sect. Denticulatae. To test this hypothesis, a cytogenetic analysis was performed with CMA/DAPI staining and fluorescent in situ hybridization using 5S and 35S rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 39 publications
4
28
1
Order By: Relevance
“…Genome sequencing has provided rich evidence that polyploidy contributed substantially to the diversification of land plants (Jiao et al, 2011; Soltis et al, 2015; Kellogg, 2016; Farhat et al, 2019; Huang and Zhu, 2019; Ibiapino et al, 2019; Sessa, 2019) and crop domestication (Salman-Minkov et al, 2016; Van Drunen and Husband, 2019). Despite near-parity of occurrence of auto- and allopolyploids among extant plants, surprisingly, and interestingly, genomic analysis showed that maize ( Zea mays ), bread wheat ( Tritium aestivum ), canola ( Brassica napus ), and the common ancestor of grasses have allopolyploid origins, with some of them as young as thousands of years (canola, ∼7,500 years, and bread wheat, ∼10,000 years) (Chalhoub et al, 2014; International-Wheat-Genome-Sequencing-Consortium, 2014; Wang et al, 2015a), while others are tens of millions of years old [maize, formed ∼26 million years ago (mya) (Schnable et al, 2009; Wang et al, 2015b), and the common ancestor of grasses, ∼98 mya] (Murat et al, 2015; Wang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing has provided rich evidence that polyploidy contributed substantially to the diversification of land plants (Jiao et al, 2011; Soltis et al, 2015; Kellogg, 2016; Farhat et al, 2019; Huang and Zhu, 2019; Ibiapino et al, 2019; Sessa, 2019) and crop domestication (Salman-Minkov et al, 2016; Van Drunen and Husband, 2019). Despite near-parity of occurrence of auto- and allopolyploids among extant plants, surprisingly, and interestingly, genomic analysis showed that maize ( Zea mays ), bread wheat ( Tritium aestivum ), canola ( Brassica napus ), and the common ancestor of grasses have allopolyploid origins, with some of them as young as thousands of years (canola, ∼7,500 years, and bread wheat, ∼10,000 years) (Chalhoub et al, 2014; International-Wheat-Genome-Sequencing-Consortium, 2014; Wang et al, 2015a), while others are tens of millions of years old [maize, formed ∼26 million years ago (mya) (Schnable et al, 2009; Wang et al, 2015b), and the common ancestor of grasses, ∼98 mya] (Murat et al, 2015; Wang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…66 sites) seems to confirm the correlation between genome size and number of rDNA sites (Prokopowich et al, 2003;Vallès et al, 2013). However, C. nevadensis, with 2n = 30 and much smaller chromosomes, had 16 rDNA sites (Ibiapino et al, 2019); therefore, this relationship is not clear for Cuscuta species.…”
Section: Heterochromatin and Rdna Sitesmentioning
confidence: 90%
“…In C. indecora and C. monogyna not all 5S and 35S rDNA sites were clearly differentiated with CMA, either because the sites were too small or because they presented a variable GC content. In three other species of Cuscuta subgenus Grammica investigated with sequential CMA/DAPI and FISH staining (Ibiapino et al, 2019), only the 35S rDNA sites were CMA + , indicating a less variable composition of their rDNA repeats.…”
Section: Heterochromatin and Rdna Sitesmentioning
confidence: 94%
See 1 more Smart Citation
“…Subgenus Grammica presents the largest variation in chromosome number and size. This subgenus has at least five cases of interspecific hybridization which can contribute to this chromosome number variation (Fogelberg, 1938; Pazy and Plitmann, 1994; García, 2001; García and Castroviejo, 2003; McNeal et al ., 2007; Ibiapino et al ., 2019; García et al ., 2019). A preliminary study of two species of Pachystigma revealed bimodal karyotypes and extensive heterochromatic blocks in the larger chromosomes, suggesting the influence of repetitive DNA in the emergence of bimodality in this subgenus (García et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%